Mental speech in the verses of judgmentday objective study - أ.م.د علاء حسين خلف (Journal of College of Education, 2023)
The Noble Qur’an mentioned the number of verses that address the human mind and alert to the judgement day, through mentioning the issues of death and the isthmus and stating their importance in a human’s ideological and intellectual life, and responding to all beliefs that suggest the annihilation of human after death and deny the resurrection and Punishment. The Quran elucidate and through Mental dialogue is that they are offered Heaven and Hell after death and before the last day